2005
DOI: 10.2337/diacare.28.3.690
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in U.S. Patients With Metabolic Syndrome, Diabetes, and Elevated C-Reactive Protein

Abstract: OBJECTIVE -C-reactive protein (CRP) independently predicts cardiovascular disease (CVD); whether it can stratify risk in those with metabolic syndrome and diabetes is not well documented. We evaluated whether elevated CRP levels modify the relationship of metabolic syndrome and diabetes with CVD in U.S. adults.RESEARCH DESIGN AND METHODS -In a cross-sectional study of 3,873 subjects (weighted to 156 million) aged Ն18 years participating in the National Health and Nutrition Examination Survey 1999 -2000, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 21 publications
9
73
2
2
Order By: Relevance
“…Elevated levels of hsCRP are also associated with an increased risk of CHD in T2DM patients [99]. In patients with metabolic syndrome and T2DM, ezetimibe added to a baseline of statin therapy reduced hsCRP significantly more (-6.5 and -15.4%) compared with addition of placebo (p < 0.05) [68].…”
Section: High-sensitivity C-reactive Proteinmentioning
confidence: 97%
“…Elevated levels of hsCRP are also associated with an increased risk of CHD in T2DM patients [99]. In patients with metabolic syndrome and T2DM, ezetimibe added to a baseline of statin therapy reduced hsCRP significantly more (-6.5 and -15.4%) compared with addition of placebo (p < 0.05) [68].…”
Section: High-sensitivity C-reactive Proteinmentioning
confidence: 97%
“…11 Recently, abundant data have emerged not only confirming the ability of CRP to add prognostic information to the Framingham Risk Score (FRS), 30,31 but also linking CRP to obesity, MS, and the development of type 2 diabetes. [12][13][14][15][16][17][18][19] Moreover, both very low (<0.5 mg/L) and very high (>10 mg/L) concentrations of CRP provide independent prognostic information on cardiovascular risk across a full range of FRS. 17 The CRP is not only an excellent biomarker of inflammation, but also a direct participant in atherogenesis and might provide a valuable tool for identifying patients at risk of cardiovascular events in primary prevention as a core part of global risk assessment, both in terms of Framingham risk evaluation and in terms of a modified MS evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the term 'metabolic syndrome' can be premature and the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) jointly stated that clinicians should avoid labeling patients with the term 'metabolic syndrome'. 10 Meanwhile, high-sensitivity C-reactive protein (CRP) has emerged as the most promising inflammatory marker which independently predicts cardiovascular risk, [11][12][13][14][15][16][17][18][19] and is considered to be an optional component of MS. [20][21][22] The CRP concentrations are proposed to be <1.0 mg/L as low risk, 1.0 to 3.0 mg/L as intermediate risk, and >3.0 mg/L as high risk for CHD in Western society. 11 However, CRP values are substantially lower in Japan than in Western countries.…”
mentioning
confidence: 99%
“…Cross-sectional studies have shown added prognostic information by risk stratification with C-reactive protein (CRP) in populations with diabetes and metabolic syndrome (4). One prospective study reported that combining metabolic syndrome and CRP enhanced the prognostic information for both future CVD and new-onset diabetes (5), whereas another prospective study showed that although CRP and metabolic syndrome were independent predictors of CVD, the combination of the two did not increase the predictive value (6).…”
mentioning
confidence: 99%